A oratória revisita a academia: pressupostos teóricos e recursos discursivos imbricados na retórica argumentativa - Azpiroz, Valneide Luciane (My University, 2017)
This doctoral thesis aims to investigate, from the corpus, the methodologies involved the main obstacles that prevent university students from producing oral texts with resourcefulness and propriety. The research starts from the concepts of oratory and rhetoric, inserting them in a historical clipping – from the Sophists Protagoras and Gorgias, crossing the philosophers Socrates, Plato, Aristotle, Cicero and Quintilian –, in order to make explicit the contributions of the precepts defended by them in the setting up of a good speaker. As far as contemporaneity is concerned, I present argumentative theories with their respective contributions to rhetorical studies, in order to arrive to the new rhetoric proposed by Perelman and Tyteca. In addition, I reflect on the place of rhetoric in Brazilian education, especially in law schools, in order to identify authors who have focused the practice of oral discourse in the national context. In the following, I explain the place that oratory occupies in the academy, bringing pedagogical and performable activities of formation, until reaching the future of oratory in university environments: here, it will be seen as the art of making subjects capable of articulating and harmonizing the ethos, the pathos and the logos, to confer effectiveness to the discourse. The results obtained reiterate the need to reinsert disciplines focused on oratory practice in the curriculum, as it will provide excellence subsidies that will enable language mastery and capacity changes, persuade and convince different audiences (sic).
Esta tese de doutoramento objetiva investigar, a partir do corpus, metodologias envolvidas nos principais entraves que impedem que estudantes universitários produzam textos orais com desenvoltura e propriedade. A pesquisa parte dos conceitos de oratória e retórica, inserindo-os em um recorte histórico – dos sofistas Protágoras e Górgias, perpassando os filósofos Sócrates, Platão, Aristóteles, Cícero e Quintiliano –, a fim de explicitar as contribuições dos preceitos defendidos por eles na configuração de um bom orador. No que tange à contemporaneidade, apresento teorias argumentativas com seus respectivos aportes aos estudos retóricos, de modo a chegar à nova retórica proposta por Perelman e Tyteca. Além disso, faço uma reflexão sobre o lugar da retórica na educação brasileira, especialmente nos cursos de Direito, de modo a identificar autores que balizaram a prática do discurso oral no contexto nacional. À continuação, explico o lugar que a oratória ocupa na academia, trazendo atividades pedagógicas de formação passíveis de serem realizadas, até chegar ao futuro da oratória em ambientes universitários: aqui, ela será vista como arte de tornar sujeitos capazes de articular e harmonizar o ethos, o pathos e o logos, para conferir eficácia ao discurso. Os resultados obtidos reiteram a necessidade de se reinserir, nos planos de execução curricular, disciplinas voltadas à prática da oratória, já que ela fornecerá subsídios à excelência que capacita o domínio da linguagem e permitirá argumentar, persuadir e convencer diferentes auditórios (sic).
Keywords: Oratória; Retórica; Ensino superior; Oratory; Rhetoric; Education, Higher